Assessing the Effectiveness of Citizenship Education Programs in Promoting Values Democratic Values - Anjaini, Risky (International Journal of Students Education, 2024)
Democracy is a decision-making process in society that ideally involves rational, inclusive, and tolerant dialogue and discussion between diverse individuals and groups. This study aims to explore the effectiveness of civic education programs in promoting democratic values through Civic Education learning in schools. Civic education emerged as an alternative, more dynamic, critical, and inclusive approach to civic education, promoted by national and state education authorities. Civic education is often a top-down and highly normative subject that encourages conformity, obedience, and passivity through static representations of society. The method used is a literature study by collecting and analyzing various related sources. Assessing the effectiveness of civic education programs in promoting democratic values is a complex and ongoing task. This study adopts a multi- method approach, builds clear indicators, and considers various factors that influence effectiveness.